If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-16+5-2x+5x=x+5
We move all terms to the left:
-16+5-2x+5x-(x+5)=0
We add all the numbers together, and all the variables
3x-(x+5)-11=0
We get rid of parentheses
3x-x-5-11=0
We add all the numbers together, and all the variables
2x-16=0
We move all terms containing x to the left, all other terms to the right
2x=16
x=16/2
x=8
| 10=1/3w | | 6(h+(1/2))-1=4h-8 | | 9f=0.5(12f−2) | | 4x+58=90 | | 2b^2+4b=0 | | 11/7=19/6x+1 | | 11x=27=4x+43 | | 2x-1+2x+2=13 | | 2.5r+11=21 | | 0.61.2c=0.6 | | -6k+k=-8+k-5k | | 5x^2=10x+4 | | 14x+5=6x+47 | | x+39+2x=90 | | 7(a-7)-4a=-3(3-a) | | 41y=40y-35 | | 5x+20=13x-20 | | 11x-19+4x-25=8x+19 | | 6(h+1/2)=4h-8 | | 11x-19+4x25=8x+19 | | 3x(x+2)=x-10 | | -31/10=-1+3/2m | | 3e=4/3 | | -9/j=-45 | | 7x+1x=2 | | 2−2s=.75s+13 | | 17-4x=7x | | 2-3-m-5=3m-5m-8-m | | 5r(6r-5)=0 | | 6z-4=3z+5 | | y/14=13 | | 2(1+5n)=82 |